Rethinking Dispute Resolution: Moi Customary Law within Indonesia’s Legal Pluralism - Rajab Lestaluhu; Sokhib Naim; Cintia Dwi Puspita; Sayed Husaini; Wahab Aznul Hidaya (JUSTISI, 2026)
This study aims to analyze the process of resolving customary land disputes among the Moi indigenous community and to identify the obstacles faced within the framework of legal pluralism in Indonesia. This study employs a normative legal research approach (doctrinal legal research), focusing on the analysis of legal norms, principles, and doctrines related to customary law and national law. Data were collected through literature review, including primary, secondary, and tertiary legal materials, and analyzed using a qualitative normative method with interpretive and comparative approaches. The novelty of this study lies in the development of a reimagined dispute resolution approach by integrating Moi customary law into the discourse of Indonesian legal pluralism, which highlights normative and socio-cultural dimensions. The results of the study indicate that dispute resolution among the Moi community prioritizes non-litigious mechanisms based on deliberation, the principles of restorative justice, and local wisdom values, with the Customary Institution (LMA Malamoi) playing a central role. However, this process faces significant obstacles, including emotional factors, low legal awareness, unclear land boundaries, overlapping ownership claims, and external intervention. This study concludes that while customary mechanisms are effective in maintaining social harmony, their interaction with the formal legal system poses challenges within the context of legal pluralism. Therefore, harmonization between customary law and state law, strengthening customary institutions, and enhancing public legal awareness are crucial for achieving fair, effective, and sustainable dispute resolution.